A Study Of Hiring Practices For Fresh Graduates From Malaysian Universities Among Public Listed Companies In Malaysia - Huey, Chin Kee (2009)
In this research project, the criteria for hiring fresh graduates from Malaysian Universities among Public Listed Companies in Malaysia will be studied. The scope of this study is limited to fresh marketing and human resource graduates from Malaysian Universities and companies listed in Bursa Malaysia. Effective approaches to learning are promoted where students are actively involved in developing their knowledge through surveys for companies.